How Well are Young Deaf Children in Early Intervention Doing on their Language Acquisition? An Assessment View - Clark, M. Diane; Wimberly, Megan B.; Goyette, Danielle; Metcalf, Holly V.; Willman, Ernest C.; Greene, Ashley; Norman, Nicholas J. (Advances in Social Sciences Research Journal, 2023)
Little is known about the earliest language acquisition of deaf children who have a variety of different experiences. Cochlear implants tend to be implanted between six months to 12 months and often become active around 18 months. In addition, Speech Language Pathologists (SLPs) tend to evaluate articulation rather than language acquisition. In terms of evaluating sign language, there are few normed assessments developed explicitly for this modality. Therefore, a joint research project was established with an early intervention program and Lamar University's Deaf Studies and Deaf Education department to evaluate the earliest language milestones acquired by deaf children between birth and five years of age. The project used language assessments developed for parents and teachers in both American Sign Language (ASL) and English, with norms derived from native users of each language. All languages reported as used by the family were assessed. Results found that most families selected spoken language and those results varied across participants. It was found that younger children using spoken language were more likely to demonstrate age-typical language acquisition when compared to older children. As more linguistic complexity developed, older children using spoken language tended to show delays. Future research suggests investigating bidirectional interactions between children, their families, and the broader systems with which the deaf child interacts. Doing so would create a further understanding of the child’s language acquisition and help families understand how to determine if their child’s language acquisition is progressing in a typical manner.